An evaluation of the socio-economic impact of timber production with and without the inclusion of biomass energy production - Ofoegbu, Chidiebere (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScFor (Forest and Wood Science))--University of Stellenbosch, 2010.